Reexamining the empirical relation between loan risk and collateral: The roles of collateral characteristics and types - Allen N. Berger; Scott Frame; Vasso Ioannidou (Federal Reserve Bank of Atlanta, 2011)
This paper offers a possible explanation for the conflicting empirical results in the literature concerning the relation between loan risk and collateral. Specifically, we posit that different economic characteristics or types of collateral pledges may be associated with the empirical dominance of the four different risk-collateral channels implied by economic theory. For our sample, collateral overall is associated with lower loan risk premiums and a higher probability of ex post loan nonperformance (delinquency or default). This finding suggests that the dominant reason collateral is pledged is that banks require collateral from observably riskier borrowers (lender selection effect), while lower risk premiums arise because secured loans carry lower losses given default (loss mitigation effect). We also find that the risk-collateral channels depend on the economic characteristics and types of collateral. The lender selection effect appears to be especially important for outside collateral, the risk-shifting or loss mitigation effects for liquid collateral, and the borrower selection effect for nondivertible collateral. Among collateral types, we find that the lender selection effect is particularly strong for residential real estate collateral and that the risk shifting effect is important for pledged deposits and bank guarantees. Our results suggest that the conflicting results in the extant riskcollateral literature may be because different samples may be dominated by collateralized loans with different economic characteristics or different types of collateral.
Keywords: G21; D82; G38; 330; collateral; asymmetric information; banks